Chronic Occupational Stress and Health Outcomes: A Systematic Review of Recent Findings - Alalhareth, Ahmed Saleh Mohammed; Alghubari, Hussain Abdullah Yahya; Alsharman, Bader Salem Mohammad; Al Faraj , Ali Mohammed Abdullah; Alyami, Hayan Mohammed Ali; Alsalem, Ibrahim Yahia Yahia; Al Bouzbedah, Hamad Mahdi; Al ajje, Abdullah Nasser Ali; Alfuhayd , Hassan Rashed Hassan; Alswedan , Mohammed Ali (Journal of Ecohumanism, 2024)
Chronic occupational stress has become an increasingly prevalent issue in modern workplaces, impacting employees across various sectors. Prolonged exposure to stress in professional settings is associated with numerous health risks, including both physical and mental health issues. Understanding these health outcomes is essential for developing effective strategies to mitigate workplace stress and promote employee well-being.This systematic review aims to synthesize recent findings on the health outcomes of chronic occupational stress, examining studies published within the last decade. By evaluating evidence from diverse occupational settings, this review seeks to identify the primary physical, mental, and behavioral health impacts of long-term workplace stress.A systematic literature search was conducted across major academic databases, including PubMed, Scopus, and PsycINFO. Studies were included if they focused on chronic occupational stress and reported on specific health outcomes. Data extraction focused on study design, population characteristics, stress measurement methods, and reported health effects. Studies were critically appraised for quality and relevance. Analysis of the selected studies revealed significant associations between chronic occupational stress and several health outcomes. Physical health consequences frequently included cardiovascular disease, hypertension, and metabolic disorders, while mental health impacts commonly involved anxiety, depression, and burnout. Behavioral outcomes, such as substance use and poor sleep quality, were also prevalent. Variations were observed across different job types and demographic factors, with certain high-risk sectors showing elevated levels of stress-related health issues.Chronic occupational stress is linked to a wide array of adverse health outcomes, underscoring the need for organizational interventions and policies to address long-term stress in the workplace. Future research should focus on longitudinal studies and targeted interventions to mitigate these health risks and improve employee well-being.